OsNAR2.1 Positively Regulates Drought Tolerance and Grain Yield Under Drought Stress Conditions in Rice - Chen, Jingguang; Qi, Tiantian; Hu, Zhi; Fan, Xiaoru; Zhu, Longlong; Iqbal, Muhammad Faseeh; Yin, Xiaoming; Xu, Guohua; Fan, Xiaorong (Frontiers in Plant Science, 2019)
Drought is an important environmental factor that severely restricts crop production. The high-affinity nitrate transporter partner protein OsNAR2.1 plays an essential role in nitrate absorption and translocation in rice. Our results suggest that OsNAR2.1 expression is markedly induced by water deficit. After drought stress conditions and irrigation, compared with wild-type (WT), the survival rate was significantly improved in OsNAR2.1 over-expression lines and decreased in OsNAR2.1 RNAi lines. The survival rate of Wuyunjing7 (WYJ), OsNRT2.1 over-expression lines and OsNRT2.3a over-expression lines was not significantly different. Compared with WT, overexpression of OsNAR2.1 could significantly increase nitrogen uptake in rice, and OsNAR2.1 RNAi could significantly reduce nitrogen uptake. Under drought conditions, the expression of OsNAC10, OsSNAC1, OsDREB2a, and OsAP37 was significantly reduced in OsNAR2.1 RNAi lines and increased substantially in OsNAR2.1 over-expression lines. Also, the chlorophyll content, relative water content, photosynthetic rate and water use efficiency were decreased considerably in OsNAR2.1 RNAi lines and increased significantly in OsNAR2.1 over-expression lines under drought conditions. Finally, compared to WT, grain yield increased by about 9.1% and 26.6%, in OsNAR2.1 over-expression lines under full and limited irrigation conditions, respectively. These results indicate that OsNAR2.1 regulates the response to drought stress in rice and increases drought tolerance.